2010
DOI: 10.3109/17453674.2010.533930
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hospital volume on length of stay, re-admissions, and complications of total hip arthroplasty

Abstract: Background and purpose Hospital volume has been suggested to be one of the best indicators of adverse orthopedic events in patients undergoing THR surgery. We therefore evaluated the effect of hospital volume on the length of stay, re-admissions, and complications of THR at the population level in Finland.Methods 30,266 THRs performed for primary osteoarthritis were identified from the Hospital Discharge Register. Hospitals were classified into 4 groups according to the number of THRs performed on an annual ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
15
1
1
Order By: Relevance
“…Following review nine of these papers were discarded for the following reasons: three were duplicates [3,8,13], two were editorials, one looked at the effect of physician owned hospitals on general competing hospitals, one looked at rural hospitals, one was a letter to the editor and one paper focused on Medicaid status. This left 21 papers of which nine were related to the knee [16][17][18][19][20][21][22][23][24], often as a more general assessment of the effect of volume on lower limb arthroplasty, and 12 looking at other aspects of orthopaedic practice [25][26][27][28][29][30][31][32][33][34][35][36]. An additional two papers [37,38] were also identified through a review of the bibliographies of identified papers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following review nine of these papers were discarded for the following reasons: three were duplicates [3,8,13], two were editorials, one looked at the effect of physician owned hospitals on general competing hospitals, one looked at rural hospitals, one was a letter to the editor and one paper focused on Medicaid status. This left 21 papers of which nine were related to the knee [16][17][18][19][20][21][22][23][24], often as a more general assessment of the effect of volume on lower limb arthroplasty, and 12 looking at other aspects of orthopaedic practice [25][26][27][28][29][30][31][32][33][34][35][36]. An additional two papers [37,38] were also identified through a review of the bibliographies of identified papers.…”
Section: Methodsmentioning
confidence: 99%
“…They calculated that if, though a greater use of higher volume surgeons, the average length of stay could be reduced to 5 days it would result in a reduction of 28,000 hospital days annually across Denmark [22]. Significantly higher lengths of stay in low volume units (b10, b50 cases per year, respectively) were seen in the studies of Lavernia [33] and Mäkelä et al [28]. This finding is supported by the work of Kreder et al [27] and Bozic et al [36] who demonstrated a shorter length of stay for patients operated on by more experienced surgeons with no alteration in outcome.…”
Section: Effect Of Volume On Morbiditymentioning
confidence: 96%
See 1 more Smart Citation
“…Given the wide range of procedures, patient outcomes and patient samples studied, the variability and inconsistency of results amongst the current literature may in part be as a result of differences in study design. A recent systematic literature review demonstrated that in regards to lower limb arthroplasties, the association between primary surgeon experience and clinical outcomes remains contentious …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic literature review demonstrated that in regards to lower limb arthroplasties, the association between primary surgeon experience and clinical outcomes remains contentious. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The ageing population has facilitated the need for an increase in the number of joint arthroplasty procedures. Total hip and knee arthroplasties are both common elective procedures that a capable trainee surgeon should be able to perform.…”
Section: Introductionmentioning
confidence: 99%